IL LIVELLO RELIGIOSO DELL'INTERSOGGETTIVITÀ NEL PENSIERO DI FICHTE - Ivaldo, Marco (Daimon Revista Internacional de Filosofia, 1994)
The essay treats the religious level of the intersubjectivity in Fichte's transcendental philosophy. The first section explain the idea of «world of reason» as ground of the indeividuality. The second moment illustrates the relation between divine and human will in the Bestimmung des Menschen. Love as radical bond between absolute and relative being is a distintive theme in Fichte's religious doctrine (third section). The fourt part treats the interesting development of Fichte's religious thought in the Staatslehre 1813 and particularly the notion of «kingdom of heaven». The intersubjectivity has in Fichte's philosophy not only a juridical and moral level but also a radical religious sense.